BRIDGING THE GAP: EXPLORING THE ROLES AND CONTRIBUTIONS OF HEALTH ASSISTANTS, NURSES, AND NURSING TECHNICIANS IN ENHANCING PATIENT CARE IN SAUDI ARABIA - Ali Hussein Almutairi, Alhemaidi Nejaikhan Al-Mutairi, Muteb Masad Ghazai Almutairi, Maryam Jurayyd Alruwaili, Faten Fahad Mohammed Alharbi, Abdullah Mohammad Salum AL hroth, Huda Sultan Saad Alyami (Chelonian Research Foundation, 2022)
Patient care is a collaborative effort that requires the contributions of various healthcare professionals. In Saudi Arabia, health assistants, nurses, and nursing technicians play crucial roles in delivering quality care to patients. This study aims to explore the specific roles, responsibilities, and contributions of these healthcare professionals in enhancing patient care within the Saudi Arabian healthcare system. A mixed-methods approach was employed, involving surveys and semi-structured interviews with health assistants, nurses, and nursing technicians across different healthcare settings in Saudi Arabia. The findings reveal that each group possesses unique skills and expertise that contribute to improved patient outcomes. Health assistants excel in providing basic patient care and support, while nurses focus on more complex clinical tasks and patient education. Nursing technicians bridge the gap between health assistants and nurses by performing a range of technical and supportive duties. The study also identifies areas for collaboration and synergy among these healthcare professionals, such as teamwork, communication, and shared decision-making. Challenges faced by each group are discussed, including workload, resource constraints, and professional development opportunities. The study concludes by offering recommendations for healthcare organizations and policymakers to support the roles and contributions of health assistants, nurses, and nursing technicians in enhancing patient care in Saudi Arabia. These include providing adequate staffing, training, and resources; fostering interprofessional collaboration; and recognizing the value of each healthcare professional's unique skills and expertise. Keywords: patient care, health assistants, nurses, nursing technicians, Saudi Arabia